The house of Lincoln : a novel - Horan, Nancy (Sourcebooks Landmark, 2023)
"An unprecedented view of Lincoln's Springfield from the acclaimed and bestselling author of Loving Frank. Nancy Horan, author of the million-copy New York Times bestseller Loving Frank, returns with a sweeping historical novel, which tells the story of Abraham Lincoln's ascendance from rumpled lawyer to U.S. president to the Great Emancipator through the eyes of a young asylum-seeker who arrives in Lincoln's home of Springfield from Madeira, Portugal. Showing intelligence beyond society's expectations, fourteen-year-old Ana Ferreira lands a job in the Lincoln household assisting Mary Lincoln with their boys and with the hostess duties borne by the wife of a rising political star. Ana bears witness to the evolution of Lincoln's views on equality and the Union and observes in full complexity the psyche and pain of his bold, polarizing wife, Mary. Along with her African American friend Cal, Ana encounters the presence of the Underground Railroad in town and experiences personally how slavery is tearing apart her adopted country. Culminating in an eyewitness account of the little-known Springfield race riot of 1908, The House of Lincoln takes readers on a journey through the historic changes that reshaped America and that continue to reverberate today"--